Historical record of Holochilus vulpinus (Rodentia, Sigmodontinae) from northern Patagonia, Argentina - Agnolin, Federico (2018)
Marsh rats of the species Holochilus vulpinus inhabit mesic and humid environments. For this reason, it is frequently used in paleoenviromental studies to infer past humid conditions. Holocene archeological record indicates that H. vulpinus had a wider geographical distribution than today. Its regional extinction in north Patagonia at the XIX century was attributed to the dry and cold Little Ice Age (LIA). Here we present the finding of a specimen of H. vulpinus from northeastern Patagonia (Valcheta stream, Río Negro province, Argentina), just at the end of LIA. Implications of this novel historical record are discussed.